The Role Of Shariah Supervisory Board On Internal Shariah Audit Effectiveness: Evidence From Bahrain - Hasnah Binti Hj Haron; Azam Abdelhakeem Khalid (Allied Business Academies, US, 2024)
Academy of Accounting and Financial Studies Journal Volume 22, Issue 5, 2018